Language and aging research: contradictions and aspirations - Bowie, David; Gerstenberg, Annette (Journal of Language and Aging Research, 2023)
With the Journal of Language and Aging Research, scholars in related fields are provided with a common venue. The newly founded journal continues and accompanies the Corpora for Language and Aging Research (CLARe) network's series of conferences started in 2014. Research in this field is confronted with major challenges, including: (1) to account for specific facets of age while not ignoring its inherent dynamics of aging; (2) to promote expertise in different related linguistic disciplines and at the same time develop its a coherent visibility; (3) to avoid stereotypes while addressing specific communicative issues in the society, as well as in families and in care institutions, covering an ever growing range of languages and varieties. The genuinely digital format is aimed at providing an open platform for innovations in the field.